Silicon recovery from diamond wire saw silicon powder waste with hydrochloric acid pretreatment: An investigation of Al dissolution behavior. (1st February 2021) - Yang, Shicong; Wan, Xiaohan; Wei, Kuixian; Ma, Wenhui; Wang, Zhi
Graphical abstract: Highlights: Si recovery from diamond wire saw powder waste is significant for Si production. The purity of recovered Si depend on the retention metallic impurity removal. The thermodynamic and kinetic mechanisms of Al dissolution was investigated. The results show that Al removal is controlled by diffusion step with Avrami model. The study provide a better understanding for Si recovery from DWSSP. Abstract: Silicon recovery from diamond wire saw silicon powder (DWSSP) waste is of great significance for increasing production profits and alleviating hazardous effects on the ecological environment. The purity of recovered silicon powder is determined by the purification efficiency during acid leaching pretreatment. Because the metallic impurities present in DWSSP are mostly physically mixed rather than chemically bound, the reaction rate is very fast in the initial stage of acid leaching, whereas it is difficult to dissolve the retained impurities in the later stage with the depletion of metal fragments adhered on the surface of the silicon matrix. Many prior studies have failed to consider the retained metallic impurities that reside in the inner silicon particle surfaces. Therefore, this study investigates the dissolution behavior of retained impurities via the dissolution of Al in HCl solution as an example. Thermodynamic results indicate that the Al dissolution process is dominated by entropic changes ( Δ S 0 ), rather than enthalpic changes ( Δ H 0 ). Furthermore, the dissolution behavior of Al is in accordance with the diffusion-controlled step in the Avrami mode, and the kinetic parameters were found to be A = 5.85 × 10 7, E a = 49.27 k J · m o l - 1, and m < 1 . The determined dissolution behavior provides a clear understanding of the removal of retained metallic impurities from DWSSP via an acid leaching pretreatment. This study provides enlightenment for the further purification of silicon recovered from DWSSP waste.